ICOS ATC CH4 Release from Norunda (100.0 m), 2017-04-01–2026-03-31 - Irene Lehner; Meelis Molder (Integrated Carbon Observation System, 2026)
Quality-controlled data on molar fraction of atmospheric CH4
Lehner, I., Molder, M. (2026). ICOS ATC CH4 Release from Norunda (100.0 m), 2017-04-01–2026-03-31, ICOS RI, https://hdl.handle.net/11676/q-5mi0XJpRfVdksVsjHyDpK5
Keywords: Atmosphere Thematic Centre; CH4; ICOS; dry air mole fraction; time instant, UTC; time instant, UTC; quality flag; quality flag; number of points; number of points; CH4 (dry air mole fraction); CH4 (dry air mole fraction); standard deviation of gas mole fraction; standard deviation of gas mole fraction; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Physical Geography; Naturgeografi; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap